Kehilangan Pasca Panen Berdasarkan Perbedaan Tata Kelola pada Rantai Pasok Paprika - Tobing, Odelia Faustina Br.; Perdana, Tomy; Sadeli, Agriani Hermita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Post-harvest losses remain a major challenge in the paprika supply chain, particularly in agricultural regions such as West Bandung Regency. Variations in supply chain governance practices across different types of suppliers are suspected to contribute to differing levels of post-harvest losses. This study aims to identify and estimate post-harvest losses in paprika under different supply chain management systems. A multi-case study approach was employed, focusing on three types of suppliers in West Bandung: farmer groups, cooperatives, and independent collectors. A qualitative method was used, with descriptive analysis of post-harvest loss estimations based on data collected through interviews and field observations. The results indicate that the highest total post-harvest loss occurred in farmer groups (3.55%), followed by cooperatives (1.82%), and the lowest in independent collectors (1.12%). These findings suggest that differences in supply chain governance significantly influence post-harvest loss levels. Losses are predominantly caused by technical issues such as improper harvesting methods, overproduction, prolonged storage, and damage during transportation. The implementation of contractual systems and strong relational ties between buyers and sellers facilitates more secure product off-take, thereby reducing losses. Meanwhile, the spot market serves as an alternative sales channel for downgraded paprika with declining quality.